Identity of Community Media Rodja Tv and Conflict Resolution in Environmental Development - Rahmah, Atikah; Novianty, Fifi (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
This research examines the role of Rodja TV Community Media as an alternative mass media in voicing the voice of Muslims and resolving conflicts in the community. In the midst of the lack of criticism of the government regarding Muslim issues in the mainstream media, community media such as Rodja TV becomes important as an alternative platform. This research aims to analyze how the influence of Rodja TV's community media identity and conflict resolution on neighbourhood development. This research uses a descriptive qualitative approach with the research subject being the community media organization Rodja TV. The theory used is making community media work: community media identities and their articulation in an Antwerp neighbourhood development project by Nico Carpentier. The results show that Rodja TV serves the community through educational programs, preaching Sunni or Salafi Islam, and social activities such as the construction of the Jami Al-Barkah Mosque. Rodja TV also plays a role in voicing the ideas of the community through various policies it makes. This research is expected to contribute knowledge about the role of community media in voicing the voice of Muslims, resolving conflicts, and encouraging environmental development. The existence of Rodja TV is proof that community media can be an effective alternative to mass media in carrying out its functions.